Physalis alkekengi L. var. franchetii (Mast.) Makino: An ethnomedical, phytochemical and pharmacological review. (10th January 2018) - Li, Ai-Ling; Chen, Bang-Jiao; Li, Guo-Hui; Zhou, Ming-Xing; Li, Yan-Ru; Ren, Dong-Mei; Lou, Hong-Xiang; Wang, Xiao-Ning; Shen, Tao
Abstract: Ethnopharmacological relevance: The calyxes and fruits of Physalis alkekengi L. var. franchetii (Mast.) Makino (Physalis Calyx seu Fructus), have been widely used in traditional and indigenous Chinese medicines for the therapy of cough, excessive phlegm, pharyngitis, sore throat, dysuria, pemphigus, eczema, and jaundice with a long history. Aim of the review: The present review aims to achieve a comprehensive and up-to-date investigation in ethnomedical uses, phytochemistry, pharmacology, and toxicity of P. alkekengi var. franchetii, particularly its calyxes and fruits. Through analysis of these findings, evidences supporting their applications in ethnomedicines are illustrated. Possible perspectives and opportunities for the future research are analyzed to highlight the gaps in our knowledge that deserves further investigation. Material and Methods: Information on P. alkekengi var. franchetii was collected via electronic search of major scientific databases ( e.g. Web of Science, SciFinder, Google Scholar, Pubmed, Elsevier, SpringerLink, Wiley online and China Knowledge Resource Integrated) for publications on this medicinal plant. Information was also obtained from local classic herbal literature on ethnopharmacology. Results: About 124 chemical ingredients have been characterized from different parts of this plant. Steroids (particularly physalins) and flavonoids are the major characteristic and bioactive constituents. The crude extracts and the isolated compounds have demonstrated various in vitro and in vivo pharmacological functions, such as anti-inflammation, inhibition of tumor cell proliferation, antimicrobial activity, diuretic effect, anti-diabetes, anti-asthma, immunomodulation, and anti-oxidation. Conclusions: P. alkekengi var. franchetii is an important medicinal plant for the ethnomedical therapy of microbial infection, inflammation, and respiratory diseases ( e.g. cough, excessive phlegm, pharyngitis). Phytochemical and pharmacological investigations of this plant definitely increased in the past half century. The chemical profiles, including ingredients and structures, have been adequately verified. Modern pharmacological studies supported its uses in the traditional and folk medicines, however, the molecular mechanisms of purified compounds remained unclear and were worth of further exploration. Therefore, the researchers should be paid more attention to a better utilization of this plant. Graphical abstract: